Pemberdayaan Masyarakat Melalui Pelaksanaan Program Keluarga Harapan (PKH) di Desa Balangtanaya Kabupaten Takalar - Nur Hidayah; A. Octamaya Tenri Awaru; Nur Ayu; Nurul Auliah. NM; Nanda Mayla Faizha Nur (Lembaga Pengembangan Kinerja Dosen, 2023)
The Hopeful Family Program (PKH) is a poverty alleviation program. This study aims to find out what forms of Family Hope Program (PKH) assistance are available, as well as the positive and negative impacts felt from the Family Hope Program (PKH) in Balangtanaya Village, Takalar Regency. As for the qualitative descriptive research method and the type of field research. The research subjects were carried out using purposive sampling techniques and the informants in this study were 5 categories, such as pregnant women, the elderly, elementary, junior high, high school. The data collected consists of primary data and secondary data. The data collection techniques and procedures used were through in-depth interviews with a number of PKH beneficiaries, observation, documentation and data recording related to the problems of this study. The results of the study describe: 1) The forms of assistance received by PKH beneficiary communities and beneficiary families include; a. Health assistance for pregnant women and children aged 0 to 6 years, b. Educational assistance for children enrolled in SD, SMP, SMA/SMK equivalent, c. Social welfare assistance for the elderly over 60 years. 2) The positive impacts felt by beneficiaries of the Family Hope Program (PKH) assistance include; a. Pregnant women, namely getting services every month such as checking the content, giving vitamins and nutrition, b. Children aged 0 to 6 years, namely the nutritional and body health of toddlers are monitored, c. Children enrolled in elementary, junior high and high school, namely fulfilling school needs, and helping to reduce the generation of children who drop out of school, d.. Elderly (Elderly), namely social protection programs, namely health services in ensuring their welfare. 3) The negative impact arising from the Family Hope Program (PKH) is that it makes some people become dependent and do not have a business to help working families to earn other income.